The Pluto system after New Horizons - Stern, Alan 1957- (The University of Arizona Press, 2021)
"Once perceived as distant, cold, dark, and seemingly unknowable, Pluto had long been marked as the farthest and most unreachable frontier for solar system exploration. The Pluto System After New Horizons is the benchmark research compendium for synthesizing our understanding of the Pluto system. This volume reviews the work of researchers who have spent the last five years assimilating the data returned from New Horizons and the first full scientific synthesis of this fascinating system"--
Keywords: Erforschung; Pluto -- Zwergplanet; Pluto (Dwarf planet); Pluto (Dwarf planet) / Exploration; Exploration of outer space; Aufsatzsammlung